Superior vena cava obstruction and pulmonary artery involvement as rare findings of immunoglobulin G4-related disease. Issue 4 (October 2021) - Behzadnia, Neda; Sheybani-Afshar, Faezeh; Sharif-Kashani, Babak; Ahmadi, Zargham-Hossein; Pourabdollah, Mihan
Abstract: We describe a case of immunoglobulin G4-related lung disease presenting as chronic pulmonary hypertension with involvement of right pulmonary artery and superior vena cava. Immunoglobulin G4- related disease is a rare systemic sclerosing disease with autoimmune entity that causes fibrotic, often mass-like manifestations that variably affect different organ systems and can be mistaken with other disorders. Timely diagnosis requires awareness on the part of clinicians and pathologists as well as radiologists to the variable manifestations of this newly recognized disorder. <Learning objective: Pulmonary hypertension is a rapidly growing field in cardiopulmonary medicine and the learning objective of this article is to highlight this relatively new subset of pulmonary hypertension and to alert the caring physicians.>